2018
DOI: 10.1016/j.jaci.2017.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Patients with atopic dermatitis and history of eczema herpeticum elicit herpes simplex virus–specific type 2 immune responses

Abstract: Biomay AG Vienna funded this work. Disclosure of potential conflict of interest: P. Colombo's institute received BIOMAY AG for this work and his institute received patents from the Italian National Research Council for other work. A. Bonura's institute received patents from the Italian National Research Council for other work. The rest of the authors declare that they have no relevant conflicts of interest. 1022-34. 2. Valenta R, Campana R, Focke-Tejkl M, Niederberger V. Vaccine development for allergen-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 24 publications
0
34
0
4
Order By: Relevance
“…185,214 Almost all EH patients are of the extrinsic AD subtype 100 , and Th2 polarization of HSV-1 specific T cells has been shown in EH patients. 215 Pretreatment with TCS does not seem to imply an increased risk of developing EH, whereas TCI may do so and should be paused for some weeks. 216 Mainstay of EH therapy is a systemic treatment with aciclovir or valaciclovir.…”
Section: Antiviral Therapymentioning
confidence: 99%
“…185,214 Almost all EH patients are of the extrinsic AD subtype 100 , and Th2 polarization of HSV-1 specific T cells has been shown in EH patients. 215 Pretreatment with TCS does not seem to imply an increased risk of developing EH, whereas TCI may do so and should be paused for some weeks. 216 Mainstay of EH therapy is a systemic treatment with aciclovir or valaciclovir.…”
Section: Antiviral Therapymentioning
confidence: 99%
“…It has been demonstrated that both T cells in AD patients in general as well as virus‐specific T cells are characterized by decreased secretion of the Th1 cytokine interferon (IFN)‐α, which is one of the reasons for the weakened immune response against HSV in AD patients. Moreover, virus‐specific T cells in patients with a history of eczema herpeticum show increased expression of Th2 chemokine receptors and elicit type 2 immune responses .…”
Section: What Are the Complications?mentioning
confidence: 99%
“…Dies ist ein Grund für die verminderte Virusabwehr gegenüber HSV bei AD‐Patienten. Zudem waren auf den virusspezifischen T‐Zellen von Patienten mit Eczema herpeticatum stärkere Th2‐Signaturen in Hinblick auf Chemokinrezeptoren sowie Immunantworten nachweisbar .…”
Section: Welche Komplikationen Existieren?unclassified